Hubungan konsumsi minuman berpemanis dengan kejadian obesitas pada anak dan remaja: A systematic literature review - Emiliana, Niti; Setiarini, Asih (Holistik Jurnal Kesehatan, 2024)
Background: Sugar-sweetened beverages are any liquid that is sweetened with added sugar in various forms. Sugar-sweetened beverages are a potential risk factor for overweight in children and adolescents. Purpose: To explore and look for scientific evidence of the relationship between consumption of sugar-sweetened beverages and the incidence of obesity in children and adolescents. Method: This research used a systematic literature review which was searched from three database sources, PubMed, Embase, and ScienceDirect. Determining search keywords based on the MeSH Term database. There were 7 journals analyzed based on inclusion criteria; they were international journals, published in the last 5 years, with a population of children and adolescents aged 5–19 years, and focused on the incidence of obesity from the consumption of sugar-sweetened beverages. Result: The serving size and frequency of consumption of sugar-sweetened beverages influence the increase in body weight changes, which have an impact on the incidence of obesity and overweight in children and adolescents. Conclusion: Consumption of sugar-sweetened beverages is associated with an increased incidence of overweight and obesity in children and adolescents. Suggestion: Further research is needed on effective solutions to reduce the consumption of sugar-sweetened beverages and address cases of obesity and overweight in children and adolescents.   Keywords: Adolescents; Children; Obesity; Overweight; Sugar-Sweetened Beverages.   Pendahuluan: Minuman berpemanis adalah segala cairan yang dimaniskan dengan tambahan gula dalam berbagai bentuk. Minuman tersebut menjadi salah satu faktor risiko yang potensial terhadap kejadian kelebihan berat badan dan obesitas pada anak-anak dan remaja. Tujuan: Untuk mengeksplorasi dan mencari bukti-bukti ilmiah hubungan konsumsi minuman berpemanis dengan kejadian obesitas pada anak dan remaja. Metode: Penelitian systematic literature review dengan pencarian menggunakan tiga sumber database yaitu, PubMed, Embase dan ScienceDirect. Penentuan kata kunci pencarian berdasarkan database pada MeSH Term. Terdapat 7 jurnal yang dianalisis berdasarkan kriteria inklusi yaitu jurnal internasional, dipublikasikan pada 5 tahun terakhir, populasi pada anak dan remaja usia 5-19 tahun, serta berfokus pada kejadian obesitas dari faktor konsumsi minuman berpemanis. Hasil: Takaran porsi dan frekuensi konsumsi minuman berpemanis memengaruhi peningkatan perubahan berat badan yang berdampak pada kejadian obesitas dan kelebihan berat badan pada anak dan remaja. Simpulan: Mengonsumsi minuman berpemanis berhubungan dengan kelebihan berat badan dan obesitas pada anak dan remaja. Saran: Diperlukan penelitian lebih lanjut mengenai solusi yang efektif untuk mengurangi konsumsi minuman berpemanis dan menangani kasus obesitas dan kelebihan berat badan pada anak dan remaja.   Kata Kunci: Anak; Kelebihan Berat Badan; Minuman Berpemanis; Obesitas; Remaja.